Hubungan Antara Andropause Dengan Insomnia Pada Pria Di Kecamatan Jebres Surakarta - Putri, Wiharesi; Iryawan, Andri; Riyadi, Slamet (Nexus Kedokteran Komunitas, 2012)
Background: Andropause represents the symptoms and signs due to the lower rate of testosteron that happened slowly along with increasing the age. One of the symptoms is vasomotor disorder, that is called hot flashes. The presence of hot flashes can be result to insomnia in males with andropause. Number ofÂ  andropauseâs prevalence which tend to high in some area in Indonesia can indicate the amount of adult men that suffer from insomnia. This research aim to prove that there is a correlation between andropause and insomnia, especially at Subdistrict Jebres Surakarta. Method: This analytic qualitative observational study uses cross-sectional method was held in Subdistrict Jebres Surakarta. Subjects in this study are males with inclusion and exclusion criterias. Sixty males (above 40 years old) were chosen to participate in this study by purposive random sampling (30 males with andropause and 30 males without andropause). Data were collected through self-administered questionnaire. Collected data were analyzed using Chi Square (X2) test and Contingency Coefficient (C) test. Result: The data analysis, with Î± = 0.05, shows p = 0.003 which means p < 0.05 and C = 0.36 or 36 %. Conclusion: There is a correlation between andropause and insomnia in males at Subdistrict Jebres Surakarta (p < 0.05, C = 0.36), where the number of insomniaâs prevalence is bigger at andropauseâs group. Keywords: andropause, insomnia, hot flashesÂ